Answer:
First expression ⇒ m + 3(m - 11)²
Second expression ⇒ m(-8m)
Third Expression ⇒ -3mn²
Fourth Expression ⇒ m - 7mn
Explanation:
* The sum of m and a n term depending on m
m added to the term 3(m - 11)²
* The product of m and a multiple of m
m multiplying by its multiple (-8m)
* The product of m and a factor not depending on m
m multiplying by (-3n²) which is a factor not depending on m
* The difference between m and a factor depending on m
(-7mn) is a factor depending on m and subtracted from m